Investigation of the removal of the diamond layer of a wheel during ed grinding with changing polarity of electrodes - Strelchuk, R. M. (Editura "Academica Brâncuşi", Târgu Jiu, 2020)
The article investigates the features of the formation of holes on the surface of a bond of grinding wheels. The impact of electrical discharges on the bonds of groups 2 and 4 causes the formation of altered surface layers with increased mechanical properties, which contribute to more durable retention of grains. The main factors affecting the thickness of the modified layer are the pulse energy, wheel rotation speed, and the amount of fluid supplied to the cutting zone. In bonds of group 1, due to the low value of the Palatnik's criterion, the electroerosive effect shapes a very developed relief, the protrusions of which have more grains. In bonds of group 3, including nonconductive components, discharges with the energy of more than 0.05J cause the appearance of cracks. Therefore, an instrument with bonds of groups 1 and 3 should be operated with pulse energy not exceeding 0.05J.
Keywords: ED grinding; diamondiferous tool layer; unit pulse; metal removal